Autonomy in learning English pronunciation: the role of portfolios - Černá, Monika (My University, 2017)
The article discusses portfolio-based autonomous learning of English pronunciation in the context of initial English language teacher education in the Czech Republic. More specifically, it introduces one possible conceptualisation of the portfolio as it was used at the University of Pardubice. This particular implementation reflects the socio-constructivist paradigm and also the reflective practitioner model of the teacher. Portfolios were deployed as a tool to strengthen coherence and integration among courses and, especially, to promote autonomy in the development of student teachers’ English pronunciation. During a one-semester course they were expected to collect evidence documenting their autonomous learning, i.e. the learning tasks which they accomplished in order to improve selected aspects of their pronunciation. The content analysis of the portfolios revealed that the student teachers targeted both segmental and suprasegmental features of English pronunciation through a considerable variety of tasks. Moreover, the analysis revealed a critical lack of autonomy, especially in relation to goal-setting and feedback strategies. In conclusion, the study acknowledged the potential of the portfolio to enhance autonomous learning of English pronunciation and also suggested possible changes in subsequent implementations of this tool.
Autonomie v učení se anglické výslovnosti: role portfolia
Keywords: English pronunciation; learning; autonomy; portfolio; anglická výslovnost; učení; autonomie; portfolio